2021
DOI: 10.1371/journal.pone.0253909
|View full text |Cite
|
Sign up to set email alerts
|

Perception of risk of exposure in the management of hazardous drugs in home hospitalization and hospital units

Abstract: Objective To assess the perception of risk of exposure in the management of hazardous drugs (HDs) through home hospitalization and hospital units. Material and methods A questionnaire was released, at the national level, to health professionals with HD management expertise. Questionnaire included 21 questions that were scored using a Likert scale: 0 (null probability) to 4 (very high probability). The internal consistency and reliability of the questionnaire were calculated using Cronbach’s alpha and the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 7 publications
0
3
0
3
Order By: Relevance
“…Health workers are exposed to the toxic effects of these HDs while preparing or administering chemotherapy ( 9 ). There are no equal measures for their protection or for the protection of patients, since the latter assume their risk of exposure to HDs to cure their disease, while it is not necessary for workers to assume that risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Health workers are exposed to the toxic effects of these HDs while preparing or administering chemotherapy ( 9 ). There are no equal measures for their protection or for the protection of patients, since the latter assume their risk of exposure to HDs to cure their disease, while it is not necessary for workers to assume that risk.…”
Section: Discussionmentioning
confidence: 99%
“…Risk assessment plays a key role in the management and control of the PM process, since all measures that are adopted to guarantee the safety of the process are based on its results. A recent study on the perceived risk of exposure in the management of HDs in hospital units ( 9 ) recommended integrating HDs into a standardized management system to improve the safety of drugs; this type of risk management model is applicable to any health center.…”
Section: Introductionmentioning
confidence: 99%
“…Hosp Domic. 2024;8(1): [29][30][31][32][33][34][35][36] Artículos especiales: Bernabeu-Martínez Ante esta circunstancia, el criterio de prudencia aconseja seguir el principio denominado ALARA (As Low As Reasonably Achievable) en lo que a exposición a este tipo de medicamentos se refiere y su objetivo es minimizar, en lo posible, la probabilidad de que se produzcan tales efectos (29) .…”
Section: Riesgos Asociados a Los Medicamentos Peligrososunclassified
“…Hosp Domic. 2024;8(1): [29][30][31][32][33][34][35][36] Medicamentos peligrosos: resumen normativo Pendiente queda, con fecha límite establecida a más a tardar 5 de abril de 2025, el establecimiento por parte de la Comisión Europea de una definición propia de MP y la elaboración de una lista a nivel europeo de MP.…”
Section: Relevancia Del Control De Los Medicamentos Peligrososunclassified
“…In the last four decades, several studies have reported detectable and/or quantifiable concentrations of such hazardous drugs both in workplaces and in biological matrices of engaged employees despite the development of suitable strategies to assess risks for healthcare workers and the adoption of preventive and protective measures [ 20 , 21 , 22 , 23 , 24 ]. However, the current lack of globally harmonized standards for the prevention of AD exposure makes such an ever-worrisome problem far from being solved and a still present occupational health priority [ 13 , 25 ].…”
Section: Introductionmentioning
confidence: 99%